The use of company fundamental, moving average and level of confidence among investor – a case of Ingress Corporation Berhad / Mohd Farids Saime - Saime, Mohd Farids (Faculty of Business and Management, 2009)
Ingress Corporation Berhad is one of the public listed company which displayed a poor financial performance for the past 5 years and simultaneously distracted investors from investing in Ingress stock. The research undertaken to study the changing trends of the decision made by investors to buy the stock despite the poor performance showed.Two methods to analyze Malaysia stock market: Fundamental and Technical. Fundamental analysis is good for long-term investments based on long-term trends, very long-term. The ability to identify and predict long-term economic, demographic, technological or consumer trends can benefit patient investors who pick the right industry groups or companies. Technical analysis is a very powerful tool and is a pre-requisite for anyone who wants to predict financial market movements and build successful trading system. Technical indicators look to predict the future price levels, or simply the general price direction, of stocks by looking at their past patterns. Examples of common technical indicators include Moving Average, MACD and Relative Strength Index (RSI).Moving Average is the basic form from all technical indicator. Both of the techniques are need of each other to identify the stock movement. Thus having both the fundamentals and technical on analysis can provide the best result for a trade and improve confidence level among investor to invest in Ingress stocks.